Membangun Pusat di Pinggiran: Pengembangan Wilayah Melalui Kerjasama Ekonomi Regional ASEAN - Baiquni, M (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1998)
From the centre, frontier region is seen as an area of underdevelopment that has not been seriously managed. The multidimensional crisis occuring in Indonesia is caused by –one of many– centralised development which has been concentrated in Java and ignores frontier areas. Efforts of developing the centre in the frontier areas have significant prospect due to economic cooperation with neighbour countries. The global era characterised by technological transformation and informational network have brought the society living in the frontier areas to the global environment. Globalisation has opened up isolation enabling the decision makers to build new centres in frontier areas in accordance to international economic cooperation. This trend of regional economic cooperation, creating new centres in the areas that were previously marginalised, can be observed in the region of ASEAN. This paper discusses aspects of the trend toward regional economic cooperation and offers policy alternatives to achieve sustainable development in this region.